Will the future maps for Australia be published by 'nobodies'. Issue 1 (2nd January 2019) - Pullar, David; Hayes, Samantha
Abstract: The web revolutionised access to map information, but it also provided new opportunities for collecting map data with crowdsourcing. The idea behind crowdsourcing is that the public are best placed to collect map data cheaply and quickly, and this could be the basis for more open and available map information. But is this feasible without authoritative oversight and can its quality be trusted? OpenStreetMap has proven it's possible and has become a popular base map in many applications. But questions remain for its future. The quality of OpenStreetMap may be understood by analysing contributor patterns of editor activity and their geographical distribution. This paper does this analysis on OpenStreetMap in Australia. We show, as others have found elsewhere in Europe and North America, that OpenStreetMap relies on a small number of dedicated contributors who change over time. We discuss recent trends for the decline of contributors and future opportunities.